Dinamika Poligami di Tengah Budaya Oligarkis-Patriarkis (Studi pada Masyarakat Poliwali Mandar dan Konawe Sulawesi) - Sadat, Anwar; Ipandang, Ipandang (Al-Manahij: Jurnal Kajian Hukum Islam, 2020)
This article attempts to look at the other side of polygamy in the context of Islamic law amid oligarchic-patriarchal culture. During this time, there are people who think the reality of polygamy as a normal action performed. But there are some state that marriage should be practiced with the true principles of monogamy. Therefore, the article focuses on the wisdom of the polygamy reality experienced by the people of Polewali Mandar district in West Sulawesi and Konawe in Southeast Sulawesi based on normative narratives. The conclusion of this article is the reality of polygamy appears inseparably from the theological and cultural foundation of value-patriarchal oligarchic. Hence, the Quranic verse interpretation greatly influences the thought and practice of marriage in a society. Like the one phrase (fa wÄá¸¥idah) in QS. an-Nisa verse 3 which is interpreted not to prohibit a polygamy but the demand to marry another wife besides the first wife if she is unable to be fair. If a man is able to be fair in the matter of material, then he is permitted to marry at least four women at the same time.